Influenza Virus and Vaccination - Nogales, Aitor (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The influenza virus poses a threat to human health and is responsible for global epidemics every year. In addition to seasonal infections, influenza can cause occasional pandemics of great consequence when novel viruses are introduced into humans. Despite the implementation of comprehensive vaccination programs, influenza viruses continue to pose an important and unpredictable global public health threat. They are one of the most significant causes of morbidity and mortality each year and have a significant economic impact. In recent years, research has been conducted to find alternative approaches to influenza vaccine development, including the generation of universal vaccines. Notably, significant progress in the field of influenza infection, transmission, and immunity have contributed to our understanding of influenza biology, and to expanding the technological approaches for the generation of more efficient strategies against influenza infections. Moreover, highly remarkable developments have been made in the implementation of new methodologies to evaluate the efficiency of vaccines and improve them for use on domestic animals such as poultry, horses, dogs or pigs. This enables us to decrease the exposure of humans to potentially pandemic viruses. The articles in this Special Issue will address the importance of influenza to human health and the advances in influenza research that have led to the development of better therapeutics and vaccination strategies.